A baseline survey on the availability of Black Bengal breeding bucks in different districts of Bangladesh - Khandoker, MAMY; Apu, AS; Husain, SS; Notter, DR (Journal of the Bangladesh Agricultural University, 2011)
The present study was conducted to assess the availability of Black Bengal breeding bucks in five districts from the Northern part (Lalmonirhat and Rangpur), Central part (Tangail and Mymensingh) and Southern part (Khulna) of Bangladesh and also to explore the relationship between distance of does from these breeding bucks and type of scarcity. The data were collected using a pre-tested questionnaire from 100 goat rearers of 100 villages in five districts. In this study, the selected characteristics of the respondents and other factors on the availability of Black Bengal breeding bucks were considered as independent variable whereas type of scarcity was considered as dependent variable. The buck and doe ratios were 1:164, 1:138, 1:114, 1:127 and 1:96 in Lalmonirhat, Rangpur, Tangail, Khulna and Mymensingh district, respectively. The pooled buck and doe ratio was 1:128. More than 70% farmers faced severe shortage of breeding bucks for serving their does in the above districts which ultimately represent the overall situation of the country. Almost all farmers (100%) had to depend on natural mating to serve their does except the farmers of Mymensingh where 12% farmers depended on artificial insemination in goat. It was observed that type of scarcity had significantly positively correlated (0.933) with distance of does from breeding bucks. This also indicated that type of scarcity gradually reached to severe level which may create the inbreeding depression in goat breeding. Keywords: Breeding buck; Black Bengal DOI: http://dx.doi.org/10.3329/jbau.v9i1.8750 JBAU 2011; 9(1): 91-96